Dos escritos judaicos até A Condição Humana: uma investigação sobre a elaboração do pensamento político de Hannah Arendt - Cabral, Michelle Silvestre (2024)
In this thesis, we investigate the process of elaboration of Hannah Arendt's political thought. Our central hypothesis is that the analysis of some of this author's biographical and existential experiences, including her Jewish origins, her academic training in early 20th-century German philosophy, as well as the persecution she suffered during World War II in Germany, in addition to her experience as a stateless person in France and the United States, can help to illuminate the genesis of her political and philosophical thought. Understanding that these were experiences that had a great impact on her formation as a thinker and that reverberate in her mature work, our goal is to evaluate the relevance of this interpretative key as an entry point to understand her political conception, particularly in the way she presents it in the work The Human Condition. Our path of research consisted of the analysis of her biography, Hannah Arendt: For Love of the World, written by Young-Bruehl; from the interpretation of the texts from her youth, collected in Jewish Writings and written since the 1930s; in addition to the examination of The Origins of Totalitarianism, from 1951; culminating in the study of the 1958 work, The Human Condition. This study allowed us to understand that the analysis of the specificity of the active dimension of human life, composed of labor, work and action, in the face of the contemplative way of life, which Arendt carries out in this work, leads her to note the necessary dimension of each of these activities for the preservation of human existence and the common world and, in particular, made it possible to circumscribe plurality as the condition for the emergence of political experience in the world. In a similar way, it provided an opportunity to verify that the inhibition or elimination of this condition, through the nullification of spontaneity and freedom of action, as exemplified in the persecution of the Jews and in Totalitarianism, puts at risk the properly human character of life, since this only manifests itself through the establishment of a common world through pluralistic interaction. By displacing the experiences and events that Arendt goes through, as well as her intellectual influences, to the circuit of elements that impact the composition of her central theses, among which are her unquestionable defense of the dignity of politics and the indispensability of updating plurality through genuine political action, we broaden the traditional scope of studies of this author. Under this light, this research allowed us to unveil the horizon in which the primary motivations that suggest and precede Arendt's later reflections emerge and corroborated the existence of important connections between her youthful writings and her mature work, expanding the possibilities of our understanding. We verified that without considering Arendt's existential-biographical context, which includes her academic training, her involvement with Zionism, her condition as a German-Jewish refugee and her confrontation with totalitarianism, it will be difficult to reach the profound elements that permeate the elaboration of her thought as well as the centrality of political reflection in it.